Determinants of Banking Firm Performance: The Role of Good Corporate Governance, Firm Size, Audit Quality, and Corporate Social Responsibility - Stevani Wijaya; Henry Gunawan (eCo-Buss, 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG), firm size, and audit quality on firm performance in the banking sector listed on the Indonesia Stock Exchange (IDX), with Corporate Social Responsibility (CSR) as a moderating variable. This research employs a quantitative approach with a causal research design to examine the relationships among the research variables. The population of this study consists of all banking companies listed on the IDX during the 2019–2023 period. The sampling technique used is purposive sampling, resulting in a total sample of 45 banking companies that meet the research criteria. The data used are secondary data obtained from companies’ annual reports, financial statements, and sustainability reports. Data analysis was conducted using the Partial Least Squares (PLS) method through the SmartPLS application, which includes validity testing, reliability testing, structural model analysis, and hypothesis testing. The results of the study indicate that Good Corporate Governance and audit quality do not have a significant effect on firm performance. In contrast, firm size has a positive effect on firm performance. Furthermore, Corporate Social Responsibility as a moderating variable is proven to influence the relationship between GCG, firm size, and audit quality on firm performance with a negative direction of influence. These findings indicate that firm size is an important factor in improving banking performance, while the implementation of CSR has not fully strengthened the relationship between corporate governance, audit quality, and firm performance in the Indonesian banking industry.